Blessings of COVID-19 Lockdown on Virtual Learning: A Higher Education Faculty Perspective - et. al., Mr. Hiteshkumar Patel, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Background: Academic iansare experiencing immensere formsglobally during lock down in COVID-19out-break.Thisstudywasintended to check how COVID-19 outbreak became blessings for higher education institute’s faculties on virtual learning and skill developmentprogramme.ItbringshowtheIndianeducationsystemhasreacted toCOVID-19pandemicsituationin thelight of E-learning. Methodology: The research methodology used was primary in nature and descriptive research design has been made use of with the review of the literature. The research was conducted among 213 academicians of higher education universities and colleges across India through structured questionnaires. This questionnaire measures the achievements of academic excellence of higher education academicians. Results: The empirical result of the study reveals that, due to the outbreak of COVID-19 many of the academician has attended and Participated in various webinars, conferences, courses, workshops, research, orientation programs, faculty development programs, etc. related to his subject for skill development. Some of the academicians have paid fees for attending virtual learning programmes. Conclusion: VirtuallearninghasdominatedtheeducationlandscapeduringCOVID-19pandemicandbecameblessedfortheprofessorsin skill development. Professors also made good use of this time and became more equipped to increase the interest and knowledgeofthestudents.Thus,ifthislockdownhasbeenablessingfortheprofessors,theprofessorswhogotocollegeafter the lockdown will seem to have become more equipped andskilled.